Stag2-mediated chromatin dynamics regulates antibody class switch recombination - Zhichen Wan; Leyi Yu; Zifan Yang; Sha Luo; Yutao Zhou; Ruolin Qiao; Hailiang Zha; Xiaoling Shan; Yifan Wang; Shuchan Li; Xuefei Zhang (Proceedings of the National Academy of Sciences, 2026)
Class switch recombination (CSR) in B lymphocytes switches immunoglobulin heavy chain ( Igh ) constant regions (C H s) to generate different functional antibody isotypes and chromatin loop extrusion has been proposed to regulate CSR. Stag1 and Stag2 are key components for stabilizing cohesin during chromatin loop extrusion, but the regulatory mechanism of Stag1 and Stag2 in CSR is unknown. Here, we reported that Stag2 is a specific cohesin component playing critical roles in promoting CSR. In contrast to the dispensable roles of Stag1 in CSR, Stag2 deficiency significantly decreases CSR without affecting DNA damage repair pathways. Mechanistically, loss of Stag2, not Stag1, significantly decreases the chromatin interaction of acceptor C H with CSR center, leading to decreased synapsis of donor and acceptor C H units, decreased transcription of acceptor C H , and impaired CSR. Notably, Stag2 deficiency significantly decreases Stag1 binding within Igh , while Stag2 could compensate for Stag1 binding within Igh upon Stag1 deficiency. Interestingly, Stag2 expression is higher than Stag1 during both mouse and human germinal center (GC) B cell development and Stag2 expression has a high correlation with CSR level in vaccinated and SARS-CoV-2-infected patients. Furthermore, Stag2 is also highly expressed in the GC B cells within different cancers, corresponding to the high level of CSR. Our findings uncover the unrecognized specific roles of Stag2 in regulating CSR.